2018
DOI: 10.1103/physrevd.97.124009
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic neutron stars in R2 gravity

Abstract: We consider static neutron stars within the framework of R 2 gravity. The neutron fluid is described by three different types of realistic equations of state (soft, moderately stiff, and stiff). Using the observational data on the neutron star mass-radius relation, it is demonstrated that the characteristics of the objects supported by the isotropic fluid agree with the observations only if one uses the soft equation of state. We show that the inclusion of the fluid anisotropy enables one also to employ more s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…(25) have been also considered. If one parameterizes the anisotropy by σ ≡ P ⊥ − P r , Folomeev [227]…”
Section: F (R) Gravitymentioning
confidence: 99%
“…(25) have been also considered. If one parameterizes the anisotropy by σ ≡ P ⊥ − P r , Folomeev [227]…”
Section: F (R) Gravitymentioning
confidence: 99%
“…(please see Refs. [1][2][3][4][5][6][7][8][9] and the references therein for reviews). The discussions of the relation of the instability of anisotropic stars with perfect fluid energy condition have been reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Then the system of Eqs. (10)-(15) has the following solutions for the metric functions (17), (18) and the anisotropic pressure…”
Section: Static Spherically Symmetric Anisotropic Solutionsmentioning
confidence: 99%
“…Recently it was shown that the "scalarization" can not arise without anisotropy and the anisotropy range can be determined by observations on binary pulsar in the Scalara e-mail: osert@pau.edu.tr b e-mail: f.celiktas@hotmail.com c e-mail: madak@pau.edu.tr Tensor Gravity and General Relativity [10]. The anisotropic star solutions in R 2 gravity can shift the mass-radius curves to the region given by observations [18]. It is interesting to note that anisotropic compact stars were investigated in Rastall theory and found exact solutions which permit the formation of super-massive star [19].…”
Section: Introductionmentioning
confidence: 99%